A public health response against Strongyloides stercoralis: time to look at soil-transmitted helminthiasis in full. - Alejandro J Krolewiecki; Patrick Lammie; Julie Jacobson; Albis-Francesco Gabrielli; Bruno Levecke; Eugenia Socias; Luis M Arias; Nicanor Sosa; David Abraham; Ruben Cimino; Adriana Echazú; Favio Crudo; et al. (Public Library of Science (PLoS), 2013)
Strongyloides stercoralis infections have a worldwide distribution with a global burden in terms of prevalence and morbidity that is largely ignored. A public health response against soil-transmitted helminth (STH) infections should broaden the strategy to include S. stercoralis and overcome the epidemiological, diagnostic, and therapeutic challenges that this parasite poses in comparison to Ascaris lumbricoides, Trichuris trichiura, and hookworms. The relatively poor sensitivity of single stool evaluations, which is further lowered when quantitative techniques aimed at detecting eggs are used, also complicates morbidity evaluations and adequate drug efficacy measurements, since S. stercoralis is eliminated in stools in a larval stage. Specific stool techniques for the detection of larvae of S. stercoralis, like Baermann's and Koga's agar plate, despite superiority over direct techniques are still suboptimal. New serologies using recombinant antigens and molecular-based techniques offer new hopes in those areas. The use of ivermectin rather than benzimidazoles for its treatment and the need to have curative regimens rather than lowering the parasite burden are also unique for S. stercoralis in comparison to the other STH due to its life cycle, which allows reproduction and amplification of the worm burden within the human host. The potential impact on STH of the benzimidazoles/ivermectin combinations, already used for control/elimination of lymphatic filariasis, should be further evaluated in public health settings. While waiting for more effective single-dose drug regimens and new sensitive diagnostics, the evidence and the tools already available warrant the planning of a common platform for STH and S. stercoralis control.